A revision of Oocyclus Sharp of Mexico and Central America (Coleoptera: Hydrophilidae) - Short, A.e.z.; Perkins, P.d. (Zootaxa, 2004)
The hygropetric genus Oocyclus Sharp is revised for Mexico and Central America. Eight species are described as new: O. catarata n. sp., O. funestus n. sp., O. grandis n. sp., O. muscus n. sp., O. ornatus n. sp., O. sharpi n. sp., O substillus n. sp., and O. tapanti n. sp. Redescriptions and new distribution records are provided for O. brevicornis Sharp, O. maculatus Sharp and O. vestitus Sharp. A lectotype is designated for O. brevicornis. A key to known Mexican and Central American species is provided. All species are associated with hygropetric habitats, including rock seeps and the spray zones of waterfalls and cascades. Digital images of the holotypes are provided (online version in color) and male genitalia illustrated.El g nero Oocyclus Sharp es revisado para M xico y Am rica Central. Ocho especies son descritas como nuevas: O. catarata n. sp., O. funestus n. sp., O. grandis n. sp., O. muscus n. sp., O. ornatus n. sp., O. sharpi n. sp., O. substillus n. sp., y O. tapanti n. sp. O. brevicornis Sharp, O. maculatus Sharp y O. vestitus Sharp son redescritas, proporcionando nuevos registros de distribuci n. Se designa un lectotipo para O. brevicornis. Se proporciona una clave para todas las especies conocidas de M xico y Am rica Central. Se proporcionan im genes digitales de los holotipos (la versi n electr nica en color) y la genitalia masculina es ilustrada para todas las especies.